KOMUNIKASI INTERPERSONAL TENAGA KERJA WANITA DALAM MEMBANGUN KELUARGA HARMONIS DI DESA WARINGIN KECAMATAN PALASAH KABUPATEN MAJALENGKA - Ningrum, Ita Puspita; Fauzi, Rifqi; Sulaiman, Anton (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
In the rapidly evolving era of globalization, the role of women in the workforce has undergone significant changes. Many women now choose to pursue careers outside the home, including working abroad as female workers. Interpersonal communication is a crucial element in building and maintaining family harmony, especially for female workers overseas. Openness, positivity, support, equality, and empathy are key to fostering strong relationships. This study aims to describe the interpersonal communication of female workers in building a harmonious family and to identify the supporting and hindering factors in interpersonal communication for female workers in Waringin Village, Palasah District, Majalengka Regency. The research employs a qualitative approach with a descriptive research type and a case study design. Data collection methods include observation, interviews, and documentation. The findings of this study indicate that effective interpersonal communication is vital for female workers to maintain family harmony despite physical distance. Openness builds trust, positivity maintains enthusiasm, support ensures attention despite the distance, equality prevents conflicts, and empathy addresses emotional needs. However, challenges such as time zone differences, parenting conflicts, guilt, and stress can hinder communication. By addressing these hindering factors, female workers can continue to maintain supportive and harmonious family relationships.